Analysis of Company Size and Leverage on Profitability - W A Astuti (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Companies that have a larger size have an effect on increasing profitability and it is expected that with a larger size, it is estimated that the company has the opportunity to attract large amounts of debt compared to small companies because the value of the assets used as collateral is greater and the level of bank confidence. is also higher, while with the use of debt (leverage), the interest paid can reduce income taxed so that profits will increase, and the use of debt can advance the company's assets which will increase the company's profitability. The purpose of this research is to examine the impact of company size and leverage on profitability, where firm size is measured by Natural Logarithm (Ln) Total Assets, Leverage is measured by Debt Equity to Ratio (DER) and Profitability is measured by Return On Earning (ROE) at Food and Beverage Sector Industrial Company listed on the Indonesia Stock Exchange. This study uses secondary data through the Annual Financial Statements obtained from the website www.idx.go.id and from the website of each company with data collection methods using purposive sampling there are 14 companies from 51 populations of food and beverage manufacturing companies listed on the Stock Exchange. Indonesia period 2016-2019. The data analysis technique uses multiple linear regression using SPSS ver 21 software. The results show that company size has a significant effect on profitability/Return on Equity (ROE). And leverage (debt to equity ratio) also has a significant effect on profitability/return on equity (ROE)